Black American Muslims: a study of religious identity and mental health - Lateef, Husain (Mental health, religion & culture, 2022)
Racism is a salient societal-level factor that adversely impacts the mental health of Black Americans. Although religiosity and racial identity have been studied in this population as protective factors, few studies have specifically considered Black American Muslims. We assessed the relationship between religious and racial identity on mental health-related factors among 499 Black American Muslims, utilising data from a cross-sectional study of Muslims in America conducted by the Yaqeen Institute for Islamic Research. Cluster analysis results indicated a five-cluster solution. Differential associations were identified between cluster membership and psychological health outcomes. Participants in profiles characterised by a belief in the low societal regard for Muslims and Blacks had significantly worse mental health than did those in other profiles. The analysis further identified religiosity, gratitude, and private regard as buffering mental health agents, with uncertainty intolerance and John Henryism being related risk factors. Implications for future research are discussed.